Tugas Kesehatan Keluarga dan Tingkat Kemandirian Keluarga di Wilayah Pesisir Kota Surabaya - Kertapati, Yoga (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2019)
Family is the smallest unit of society that has a large influence on the health of each member of his family. The family is the focus of the approach in implementing the â€œProgram Indonesia Sehatâ€. Families have assignments in the health sector to improve and maintain family health. One aspect that becomes a benchmark is the level of family independence. This study used a cross-sectional design with a sample of 150 families. Data analysis using the Spearman rho correlation test. The results showed that there was a positive correlation between family health duties and the level of family independence (r = 0.630, p = 0.000). Based on the results of this study, it is expected to be input and information about family health tasks as a measure of success in increasing family independence when providing family nursing care.Â Keywords: Family, Health Assignments, Level of Independence